Análise descritiva de duas traduções para o português de Orgulho e preconceito, de Jane Austen, com foco na ironia da personagem Elizabeth Bennet - Azevedo, Manoela Lima (2023)
This paper aims to analyze two translations into Brazilian Portuguese of Pride and Prejudice, a classic of world literature, by English author Jane Austen. The translations chosen for this analysis were that of Lúcio Cardoso, published in 1940, and that of Alexandre Barbosa de Souza, in 2011. In order to situate the reader of this research regarding the historical context in which the novel Pride and Prejudice was published, we address the main facts of England in the nineteenth century. Regarding the author, we elaborated a biobibliography of Jane Austen combining the facts of her life with the publications of her novels and other written productions, based on the studies of Fabiny (2017), Wilson (2017), White (2016), Reef (2014) and Austen-Leigh (2014). Also, we highlighted the role of the writer and of the novel in the world literary scene. This research contemplates the area of Translation Studies by bringing the ideas of Holmes (1988) and is based on Descriptive Studies, using the theories developed by Even-Zohar (1978), Toury (1981), and mainly, Lambert and Van Gorp (1985). The two theorists proposed the translation analysis model used in this paper, which investigated three aspects of the two translations: the preliminary data, the macrostructure level, and the microstructure level. Based on these levels, we investigated and described the translators' choices, seeking to understand the strategies adopted by each one in relation to the English source text. In order to delimit the corpus of analysis investigated at the microstructural level, we selected 10 lines from the character Elizabeth Bennet, the protagonist of this novel, that contain the irony procedure, so present in Austen's production. The lines express Bennet's ironic side, in her constant criticism of the human types that surrounded her and the 19th century society in which she lived. To understand how irony is used by Jane Austen, we used the studies of Sørbø (2014), Shapard (2012), DeWilde (2010), Mateo (2010), and Moses (2003). From this research, we found the presence of translation strategies such as transposition, omission, addition, modulation, and borrowing. Also, we concluded that the norms of the target text are predominantly used by the translators in the utterances chosen for analysis, categorizing the translation as acceptable.